2015
DOI: 10.1002/pssa.201532182
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of nitrogen into polycrystalline diamond surfaces by RF plasma nitridation process at different temperatures: Bonding configuration and thermal stabilty studies by in situ XPS and HREELS

Abstract: In situ studies of low energy nitrogen species incorporated into diamond films are significant as they could lead to a better understanding of bonding configuration and defects formation of the modified surface. In this report, we investigate the interaction of radio frequency (RF) nitrogen plasma onto a polycrystalline diamond surface at different temperatures (RT, 250, 500, and 750 8C). The influence of RF nitridation temperature on the bonding configuration, thermal stability, and concentrations of incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 44 publications
4
16
1
Order By: Relevance
“…For each case, we identify the favored adsorption geometry by total energy calculations and evaluate the nature of surface bonding by analyzing the density of states (DOS) and the corresponding charge distribution. Further calculations of the vibration of the adsorbed nitrogen species and the 1s core-level shift of surface carbons are complementary to the recent works that used HREELS and XPS, calling for re-interpretation of some spectrum features in the literature. Lastly, we present simulated images of adsorbed nitrogen species on diamond(001), in preparation for future work using scanning tunneling microscopy (STM). Our results highlight the flexibility of the nitridation of diamond surfaces, offering opportunities of controlling both the number and charge state of the shallow NV centers in the layer-by-layer construction of diamond-based devices.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…For each case, we identify the favored adsorption geometry by total energy calculations and evaluate the nature of surface bonding by analyzing the density of states (DOS) and the corresponding charge distribution. Further calculations of the vibration of the adsorbed nitrogen species and the 1s core-level shift of surface carbons are complementary to the recent works that used HREELS and XPS, calling for re-interpretation of some spectrum features in the literature. Lastly, we present simulated images of adsorbed nitrogen species on diamond(001), in preparation for future work using scanning tunneling microscopy (STM). Our results highlight the flexibility of the nitridation of diamond surfaces, offering opportunities of controlling both the number and charge state of the shallow NV centers in the layer-by-layer construction of diamond-based devices.…”
Section: Introductionmentioning
confidence: 68%
“…Despite the valuable insight gained from the prior works, there remains some ambiguity around the nitridated diamond surfaces, such as the composite, structure, and chemical state of the adsorbed nitrogen species. Here, we present DFT studies on the adsorption of representative nitrogen species (N, NH, and NH 2 ) on bare and hydrogenated diamond(001) surfaces, aiming to shed light on the atomistic description of the nitridated diamond surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently demonstrated that high-quality N-terminated diamond (100) surface can be realized by using an indirect radio frequency N 2 plasma process that keeps the surface damages minimal caused by the plasma treatment. , Those samples were grown at temperature of ∼700 K with a pressure of nitrogen source at 170 Torr. The predominant component is substitutional nitrogen or mixed N/CH species at the surface, depending on the type of diamond substrate where the fraction of nitrogen termination reaches at least 0.5 ML.…”
mentioning
confidence: 99%
“…This was further complemented by Fabry et al [ 130 ] who reported that thermal plasma induced by DC or AC plasma torches is an adequate method for the conversion of waste to energy and can certainly be used for the remediation of numerous wastes including municipal solid wastes, heavy oil, used car tires and medical wastes by gasification processes. On the other hand, Chandran et al [ 131 ] investigated the efficiency of radio frequency (RF) plasma on nitridation that involved the incorporation of nitrogen onto the surface of the polycrystalline diamond at varied temperatures (250, 500, 750, 1000 °C). The results of their research showed that nitrogen content in the diamond surface declined with an increase in temperature during the nitridation process.…”
Section: Overview Of the Plasma Processmentioning
confidence: 99%